Vous êtes sur la page 1sur 11

R + R +

f (x) = x R +

x

lim xd f(x) lim xd+ f(x) f (x) = x 2

=

+∞ − ∞ 0 . 0/0 /

 

u + v

u + v

ku R

. u

u . v

u . v + u . v

1

u

u

u

u

u . v u . v

v

v 2

f (x) > 0 f (x) < 0 f (x) = 0 f

( dx ) 2

d 2 f

df

dx

2

g(x) = f (u(x)) g = f u u(x) f g (x) = u (x) . f (u(x)) f (u) u u x u (x)

g(x) =

1

1 + x 2

f (u) = 1/u u(x) = 1 + x 2 u(x) f (u) u u x

f (u) = 1 2 =

u

1

(1 + x 2 ) 2

u (x) = 2x

g (x) =

2x

(1 + x 2 ) 2

ln|f | f /f f = (ln|f|) . f

f(x) = (x + 1) 4

(x 3) 5

ln|f |

ln(| (x + 1)

(x

4

3) 5 |) = 4ln(|x + 1|) 5ln(|x 3|)

f

f (x) = (

4

x 3 ) . (x + 1) 4

(x 3) 5

5

x + 1

f − 1 f ◦ f − 1 f ( x ) = x f

f 1 f f 1 f (x) = x f f y = x f : E F f f (x) = x 2 R + f R + R a 2 a a f R + R +

f 1 (x) (f (x)) 1 = 1

f(x)

f 1 (y) = x f 1/f (x)

(f 1 ) (y) =

1

f (f 1 (y)

g(x) = x g(x) = f 1 (x) = x g 1 (x) = f(x) = x 2

g (x) = (f 1 (x)) =

1

1

1

f (f 1 (x)) = f ( x) =

2

x

 

e

x

 

ln

  e x   ln   R   R + e a e b = e
  e x   ln   R   R + e a e b = e

 

R

 

R

+

e a e b = e a+b

ln(ab) = ln(a) + ln(b)

e

a

ln( a ) = ln(a) ln(b)

b

ln(a b ) = b . ln(a)

= e ab

e b (e a ) b = e ab

 

e

x

 

1/x

 

 

]0; 1] [1; +[

lim x (e x ) = 0

lim x0+ (ln(x)) = −∞

lim x+ (e x ) = +

lim x+ (ln(x)) = +

lim x+( e

x

x ) = +

lim x (x . e x ) = 0

lim x+( ln(x)

x

) = 0

e x e x

lim x0+ (x . ln(x)) = 0

a > 0 log a (y) y = a x x = log a (y)

log 10 = log

log a (y) = ln(a) ln(y)

k x kx x klog a (x) k log a (0) = −∞

log(1) log(2) log(3) log(1) = 0 log(2) x f (x) = log(30) y = 30

log (3) log (1) = 0 log (2) x f ( x ) = log (30)

E = A + B . log(D) R A/B

R A/B =

R A/B > 1 R A/B < 1 R A/B = 1

x x 0

f(x) f (x 0 )(x x 0 ) + f(x 0 )

(x 0 ; f(x 0 ))

(x 1 ; f(x 1 ))

) + f ( x 0 ) ( x 0 ; f ( x 0 ))

x f (x)

f(x) f(x 0 )

x x 0

f(x 1 ) f(x 0 )

x 1 x 0

f(x) f(x 0 ) + f(x x 1 1 ) f(x x 0 0 )

. (x x 0 )

f(x) f(x 0 ) + (x x 0 ) . f (x 0 ) + (x 2! x 0 ) 2 . f (x 0 ) +

+ (x n! x 0 ) n . f n (x 0 ) +

x 0 = 0 f (x) x x 0